Efficiency of selenium ion inclusion into common carp (Cyprinus carpio L.) diets - Magdy M. Gaber (Advances in Aquaculture and Fisheries Management, 2017)
Efficiency of the increase diets nutritional value by adding selenium as microelement into diets common carp fingerlings were studied using aquarium and cement tanks systems, which allowed feeding and continues measurement of growth parameters. In experiment (I) one hundred and fifty fingerlings each weighing approximately 7.5 ± 0.23 g was carried out, in aquarium and fed either normal diet (group A) or diets supplemented with 0.08, 0.16, 0.32 and 0.64 mg kg -1 of sodium selenite. In experiment (II) three hundred and sixty juvenile common carp, average weight 26.9 ± 1.38 g was carried out in cement tanks and fed as in experiment (I). When selenium added to the diets and fed to the fish caused a significant increase in weight gain and carp fingerlings growth rate was accelerated by 18-22% feed expenditure out by 17-18% as compared to the control diet. Significant differences in survival rate were found between treatments, indicating that diets are likely to be responsible for increased survival rate, observed in fish fed diets supplemented with 0.24 and 0.32 mg kg-1 sodium selenite (0.12 and 0.15 mg kg-1 selenium). The results of this study indicated that a diet supplement, 0.24 and 0.32 mg kg-1 of sodium selenite (0.12 and 0.15 mg kg-1 selenium), is important for growth and survival of common carp.